PHENOTYPIC AND MARKER ASSISTED EVALUATION FOR PATHOGENICITY AND AGGRESSIVENESS OF ROMANIAN FUSARIUM ISOLATES VS. WHEAT - Ittu, M.; Cana, L.; Ciuca, M.; Voaides, C.; Cornea, P. (Plant Breeding and Seed Science, 2011)
Pathogenicity and aggressiveness vs. wheat of 30 new Fusarium accessions, primarily F. graminearum, obtained from random naturally infected grain samples of bread wheat, durum wheat and triticale collected across Romania, phenotypically and by molecular tools has been investigated. A large variation of this trait, expressed as reduction of coleoptiles length (% of control), in seedling stage, on average over three varieties, ranging from 2.1 to 30.9 % was registered. Point field inoculations at anthesis of 90 Fusarium isolate x wheat varieties combinations, revealed also the variability of several components of aggressiveness: severity (14.4-64.8%), AUDPC (104.9-527.1), and FDK 8.1- 43.7%, respectively. Molecular techniques allowed identification of Fusarium species and the analysis of polymorphism within fungal isolates. Moreover, the presence of TRI 5 gene involved in DON biosynthesis was detected in the majority of isolates. Similarity between records obtained in seedling and adult stage for the most aggressive of Fusarium isolates, suggests that phenotypic selection in conjunction with molecular tools could be a reliable method to select the appropriate pathogen strains for breeding of resistance.